The Effect of leather fibers on the properties of rubber-leather composites - Maria J. Ferreira (2010)
Finished leather waste resulting from footwear production is mainly managed by landfilling, thus wasting the contained resources. Recycling by incorporating these wastes in new composites would be a more sustainable option. In this work, styrene butadiene rubber and acrylonitrile butadiene rubber based compounds were charged with <= 1 mm leather fibers in the range of 12.5-300 parts per hundred parts of rubber (phr). Rubber-leather composites were vulcanized by compression molding and characterized regarding possible footwear functional applications as soles and in-shoe parts. The results obtained indicate that up to 10-20 phr of leather incorporation composites with improved tear strength are obtained. Tension and elongation decrease, but within the acceptable range for application. The remaining physical properties studied in these composites are not significantly influenced, and consequently, they are adequate for soles application. Above the referred range of incorporation and till 100 phr the composites properties are compatible with in-shoe components application.